Experimental investigation of two-phase slug flow distribution in horizontal multi-parallel micro-channels. (2nd February 2017) - Liu, Yanchu; Sun, Wanchun; Wang, Shuangfeng
Abstract: A visualization experimental study was conducted to investigate the phase distribution of two-phase slug flow in horizontal multi-parallel micro-channels, which was composed of a header with hydraulic diameter of 0.667 mm and three parallel channels with hydraulic diameter of 0.500 mm, all with rectangle cross section. Nitrogen and 0.03 wt% sodium dodecyl sulfate (SDS) solution were used as the test working fluids. The inlet superficial velocities of gas and liquid varied from 0.130 to 1.47 m/s and from 0.128 to 0.900 m/s, respectively. The high speed recording technique was utilized to elucidate the fluid dynamics of two-phase flow in parallel micro-channels. It was found that the phase distribution characteristics of two-phase flow in parallel channels highly depended on the inlet gas slug length and the inlet real velocity, and the channels in the front of the header can influence the phase distribution of the adjacent channel in the rear. Moreover, a uniform phase distribution was achieved at high real velocity with short gas slugs. Highlights: The phase distribution of two-phase slug flow in three parallel micro-channels was visually investigated. The behavior of two-phase slug flow at the entrance of branch channels was analyzed. The effects of inlet gas slug length and inlet real velocity on phase distribution were studied. A relatively good phase distribution was obtained with short inlet gas slug length and high inlet real velocity.